2022
DOI: 10.1002/adpr.202100263
|View full text |Cite
|
Sign up to set email alerts
|

Optically Pumped Terahertz Molecular Laser: Gain Factor and Validation up to 5.5 THz

Abstract: Quantum cascade laser‐pumped terahertz (THz) gas lasers are at the edge of revolutionizing THz science where powerful yet tunable sources have long been lacking. Maybe one of the last remaining drawbacks to a wider use of these instruments lies in the lack of available databases of potentially lasing transitions for users. A new figure of merit, the molecular gain factor is proposed, that allows to discriminate transitions by their lasing potential. Using this factor, catalogs of THz laser lines of ammonia, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In order to design a laser, experimental values of the gain for each transition are needed even if the gain factor can be estimated using databases [4]. Gain values were previously measured for two transitions [5] and showed that the gains were the highest measured in a continuous wave pumped gas.…”
Section: Methods and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to design a laser, experimental values of the gain for each transition are needed even if the gain factor can be estimated using databases [4]. Gain values were previously measured for two transitions [5] and showed that the gains were the highest measured in a continuous wave pumped gas.…”
Section: Methods and Experimental Resultsmentioning
confidence: 99%
“…Figure 4 shows a summary of the measurement of the gain of six pure inversion transitions of NH3 for the same pump power density Pp and pressure (20 µbar) versus the molecular gain factor Gm defined in [4] and calculated using the HITRAN database. The red line shows a fit considering a relaxation rate Γ of 2.5x10 -5 s -1 .…”
Section: Methods and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, generating and detecting THz radiation is still a challenging task due to the lack of efficient and compact sources and detectors. At present, different approaches for THz generation have been explored, such as optically pumped molecular gas terahertz laser [4], quantum cascade laser [5], photoconduction [6], and free-electron lasers [7]. Each of those methods presents limitations mainly related to costs, dimensions, environmental working parameters, and thus in general low applicability.…”
Section: Introductionmentioning
confidence: 99%